La informalidad tributaria en los comerciantes de la casona del mercado Bélen de la ciudad de Iquitos, periodo 2021 - Paredes Barbaran, Greysi Malu (2022)
Tax informality is a phenomenon immersed within a society, and it is mainly caused by the ignorance that merchants present in regulations related to tax matters, also generating an evasion in the fulfillment of their tax obligations, a situation that directly affects the level of collection tax be the State. The present investigation entitled “The tax informality in the merchants of the Casona of the Belén market of the city of Iquitos, period 2021”, had as a general objetive to determine the level of tax infomality presented by the merchants of the Casona of the Belén market of the city of Iquitos, period 2021. Likewise, the research was of a quantitative type and of a descriptive non-experimental-cross-sectional design. From the analysis and discussion of the result obtained, it was possible to determine that the level of informality present by the merchants of the aforementioned market is high.